Anti-inflammatory effect of Perilla frutescens seed oil rich in omega-3 fatty acid on dextran sodium sulfate-induced colitis in mice - Napapan Kangwan; Komsak Pintha; Chakkrit Khanaree; Sarawut Kongkarnka; Teera Chewonarin; Maitree Suttajit (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Ulcerative colitis is a chronic inflammatory bowel disease that involves diffused inflammation of the large intestine. Omega-3 fatty acid (FA) has been known to regulate the inflammatory response associated with ulcerative colitis pathogenesis. Perilla frutescens is a valuable source of omega-3 FA and α-linolenic acid (ALA) contained in its seed oil. Therefore, the aim of this study was to evaluate the anti-inflammatory effect of Perilla seed oil (PSO) on colitis induced by dextran sulfate sodium (DSS) in a mouse model. Experimental approach: PSO was extracted using a cold-pressed extractor and FA composition of PSO was analyzed by GC-MS. Acute colitis in mice was induced with 3% DSS in drinking water for 7 days. Some mice were treated with PSO (20, 100, 200 mg/kg BW) for 3 weeks before the DSS administration. Sulfasalazine was used as a positive control. The clinical features, histopathologic, serum, and gene expression of proinflammatory cytokines in the colon were assessed. Finding/Results: PSO contained the highest proportion of ALA (61.51%). Furthermore, PSO pretreatment evidently reduced body weight loss, diminished diarrhea, gross bleeding, and DSS-induced colon shortening. PSO pretreatment attenuated histopathological changes in response to DSS-induced colitis. PSO pretreatment also markedly decreased inflammatory response in serum and the colon tissue of DSS-induced mice. Conclusion and implication: ALA in PSO is suggested to be mainly responsible for the reduction of DSS-induced colitis through suppressing inflammatory markers. PSO could be further developed as a functional health supplement, which would be beneficial for anti-inflammation in the colonic mucosa.